Mitral annular calcification in patients with significant mitral valve disease: An old problem with new solutions - Ascione, Guido; Denti, Paolo (Frontiers in Cardiovascular Medicine, 2022)
Mitral annular calcification (MAC) is a chronic process involving mitral valve annulus, linked with an increased cardiovascular mortality and morbidity. Since its first autoptic description, a progressive evolution in diagnostic tools brought cardiac CT scan to become the gold standard in MAC detection and classification. The treatment of significant mitral valve disease in patients with annular calcifications has always represented an issue for cardiac surgeons, being it linked with an increased risk of atrioventricular groove rupture, circumflex artery injury or embolism. As a consequence, different surgical techniques have been developed over time in order to reduce the incidence of these fearsome complications. Recently, transcatheter mitral valve replacement has emerged as a valid alternative to surgery in high-risk patients. Both hybrid transatrial, transfemoral or transapical approaches have been described to deliver balloon-expandable or self-expanding aortic transcatheter valves into the calcified annulus, with conflicting early and long-term results. Tendyne (Abbott Structural Heart, Santa Clara, California) is emerging as a promising, transapical delivered option. Early results have shown effectiveness and safety of this device in patients with MAC and severe mitral valve disease, with the lowest rate of embolization, mortality and left ventricular outflow tract obstruction reported so far.